Measuring Critical Thinking Skills through Performance Assessment: The Profile of EFL Students’ Critical Thinking Skills - Jumariati, Jumariati; Asrimawati, Inayati Fitriyah; Mulya, Jauza Naja; Taka, Deo Deo Laki (JEES (Journal of English Educators Society), 2024)
This study tries to find the profiles of EFL students' critical thinking skills in writing problem-solution expository essays within wetland themes. It employs a descriptive design with quantitative approach by utilizing a validated writing test. The subjects of the study were 40students of the English Language Education Study Program of the University of Lambung Mangkurat, Indonesia, who were enrolled in the Academic Writing courses. The essay produced by each student was measured based on the depth of cause-and-effect analysis, the logic of the argument given, the viability of the solution, and the validity of evidence used to support the argument. The findings reveal that the subjects’ critical thinking skill is categorized as medium since the mean score on the test of critical thinking is 11.38. Particularly, they have a high level of critical thinking in the aspects of analyzing the issue (3.03) and providing viable solutions (3.18). It indicates that they are able to distinguish the cause of a problem and the consequences as well and consider the causes and consequences when they propose a solution. However, their skill in providing argument is medium (2.85) whereas their skill in providing the evidence is low (2.33). These findings suggest that the subjects need to be trained in providing arguments and sufficient evidence through leading questions, discussion, and reading relevant sources. It implies that the study program needs to develop a teaching model that facilitates the students to practice their critical thinking skills. HIGHLIGHTS : The indicators of critical thinking measured in the writing performancetest consist of: (1) the depth of cause-and-effect analysis, (2) the logicof the argument given, (3) the accuracy of the solution offered, and (4)the validity of evidence used as support for the argument One of the possible challenges in developing EFL students’ criticalthinking skills is their English proficiency. Those who are less proficientmay struggle more in expressing ideas while providing argumentscompared to those who are more proficient. This eventually affectstheir skills in reasoning. The findings of the study imply the need to provide EFL students withguidance such as questioning strategy, discussion, and relevant sourcesof information to practice their critical thinking skills while developingtheir English language skills.